Learning Ecological Fiqh Through Reog Media in Improving Environmental Care Character in The Merak Ponorogo Conservation Area - Katni Katni; Ana Mizatul Laila; Mela Fadila; Alvina Rahma Fitria; Janu Adi Prastyo; Endang Septi Riyansih (Assyfa Journal of Islamic Studies, 2025)
This research is motivated by academic challenges such as low ecological awareness among students and the continued dominance of normative Islamic jurisprudence (fiqh) learning that lacks contextualization of environmental and local cultural issues. On the other hand, the Reog culture of Ponorogo possesses ecological symbolic value that has the potential to be used as a learning medium for Islamic Religious Education based on environmental conservation. This study aims to analyze the implementation of ecological fiqh learning through Reog, the internalization of ecological values ​​in Reog cultural symbols and practices, and the enhancement of students' environmental awareness in the Ponorogo peacock conservation area. The study employed a qualitative approach with a case study approach using participatory observation, in-depth interviews, and documentation. Data analysis was conducted using the Miles and Huberman interactive model, with source and technique triangulation to test data validity. The results indicate that ecological fiqh learning through Reog is implemented contextually through field observations, environmental conservation practices, and ecological cultural reflection, making learning more meaningful and applicable. The ecological values ​​of the peacock symbol have been successfully internalized as a representation of ecosystem balance, wildlife conservation, and human responsibility as khalifah fil ardh (vicegerents on earth) in preserving the environment. Furthermore, learning based on local culture and environmental conservation has been proven to enhance students' environmental stewardship, demonstrated by increased concern for cleanliness, reforestation, wildlife conservation, and active involvement in community-based conservation activities. This research confirms that the integration of Islamic education, local culture, and environmental conservation can be a transformative learning model in shaping students' ecological character in a reflective, participatory, and sustainable manner.